Resurrection ecology of invertebrates in temporary wetlands in the Cape Floristic region: effects of urbanisation and fire - Blanckenberg, Michelle (Department of Biological Sciences, 2017)
Despite their importance to regional biodiversity, temporary wetlands and their invertebrate communities are generally understudied and under-conserved. Resurrection ecology is used to study the communities present in the dry phase of temporary wetlands to gain a better understanding of the functioning and health of these systems. The hatching success of invertebrate propagules in dried soil sediments, collected from temporary wetlands in Cape Sand Fynbos regions of Cape Town, were investigated in 2016. Soil samples were collected from conserved and urban sites (during May and June 2016) using a standard soil auger method and complemented with monthly aquatic phase sampling using standard sweep net methods (during September and October 2016). The effects of fire were tested, on hatching success by staging vegetation fires over the collected soil samples for five temporary wetland areas in the same region. Mann-Whitney U tests were used to test differences in abundances between treatments, whereas for comparison of taxon richness, Shannon diversity and Pielou's evenness linear mixed effect models (LMER) were used. Non-metric multidimensional scaling (nMDS) plots were used to graphically visualize the community composition between the different treatments, with 'adonis' analysis used to test their statistical significance. Results found a total of 18 invertebrate taxa hatched, while a total of 27 taxa were identified from the wet phase. Results from hatching assays showed no significant differences in diversity patterns of invertebrates between conserved and urban areas in the dry phase. However, wetlands that were in the conserved area supported higher invertebrate diversity during the wet phase, although not significant (lmer, Z = -1.75, p = 0.08). These results suggest that human activity (alien vegetation, littering and polluting) in the area did not impact the ability of invertebrate propagules to emerge, but did slightly affect the natural aquatic phase. Fire had a significantly negative impact on invertebrate diversity measures (lmer, p < 0.001) and community composition (adonis, F = 24.494, p = 0.001) during hatching assays. Management of unpredicted and uncontrolled fire in urban areas is essential to ensure future protection of critical biodiversity areas created by these temporary wetlands. More research should focus on the impact of increasing fire frequency and intensity on these systems to understand the management challenges in a changing climate.